Employee Performance is Assessed from Homebase Work Placement, Transfers, Motivation, and Career Development - Jendra Purusha Hayuningrat; Sarsono Sarsono; Bambang Mursito (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2026)
Good employee performance​ will contribute to achieving revenue targets taxes which are one of the focus main Directorate General of Taxes. Research This done For (1) Testing and analyzing influence placement home base to performance employees, (2) Testing and analyzing influence mutation to performance employees, (3) Testing and analyzing influence motivation to performance employees, (4) Testing and analyzing influence development career to performance employees. This research is a descriptive analysis type with a quantitative approach, namely research that analyzes data with centralize attention to existing symptoms​ characteristics certain in life the human being named variable. This research will be conducted at the Central Java II DJP Regional Office. The population in this study is all employees at the Central Java II DJP Regional Office, totaling 158 employees. This research was conducted at the Central Java II DJP Regional Office, researchers took a sample of 50% of the total population, namely 79 employees. The sampling technique in this study used a non- random sampling technique. The regression coefficient and t-test values show that the career development variable has the highest value compared to other variables, meaning that career development has the most dominant influence on employee performance. The results of the research that has been conducted state that (1) Homebase work placement has a positive and insignificant effect on employee performance, (2) Mutation has a negative and significant effect on employee performance, (3) Motivation has a positive and significant effect on employee performance, (4) Career development has a positive and significant effect on employee performance. Keywords: Career, employee performance , Homebase work placement, Mutation, Motivation,